2017
DOI: 10.1016/j.ijdevneu.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dipyrone treatment during lactation in mice reduces maternal behavior and increases anxiety‐like behavior in offspring

Abstract: Dipyrone (metamizole), a powerful drug, is widely used as an analgesic and antipyretic; however, the safety of its use during lactation and the potential impact on the offspring are not well established. This study aimed to determine the effect of maternal dipyrone treatment during lactation on offspring development and emotional behavior and on the dam's maternal behavior. Hence, on postnatal day (PND) 2, drinking water only or drinking water containing dipyrone at doses of 100, 300, and 500mg/kg/day, were of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Their offspring (40 female and 40 male mice from each group) were used for the experimental procedures during adolescence (PND 30‐32). To avoid the litter effect, one couple (1 male and 1 female mouse) from each litter received an ink mark on one hind limb for observation of reflex parameters and physical development until PND 21 (n = 10 per group) (Veronesi et al, 2017). The other three couples of each litter that were not marked were used to evaluate the behavioral performance in the light dark, open field, or play behavior tests (n = 10 per group) during adolescence since each animal was used only once for a given behavioral evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their offspring (40 female and 40 male mice from each group) were used for the experimental procedures during adolescence (PND 30‐32). To avoid the litter effect, one couple (1 male and 1 female mouse) from each litter received an ink mark on one hind limb for observation of reflex parameters and physical development until PND 21 (n = 10 per group) (Veronesi et al, 2017). The other three couples of each litter that were not marked were used to evaluate the behavioral performance in the light dark, open field, or play behavior tests (n = 10 per group) during adolescence since each animal was used only once for a given behavioral evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…The mean number of days required for the appearance of each of the above‐mentioned parameters was calculated. On PND 21, the offspring were weaned, marked with a nontoxic ink, distributed in accordance with their sex, and housed in groups of four per cage (Carvalho et al, 2016; Veronesi et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…USVs in infant rodents can be affected by genetic, pharmacological, or early-life environmental manipulations, such as chronic stress. Infant USVs during maternal separation are also correlated with anxiety-life behaviors in later life (Barua et al, 2014;Trezza et al, 2008;Veronesi et al, 2017), as was the case with gestational exposure to BPA. However, there have been no other reports on infant USVs in a BPA exposure model.…”
Section: Ultrasonic Vocalizationsmentioning
confidence: 78%
“…Rats selectively bred across many generations for high levels of USVs during maternal separation demonstrate significantly more anxiety and depressive-like behaviors in later life (Brunelli and Hofer, 2007;Dichter et al, 1996). Several other studies have also shown positive associations between pup USV calling and anxiety/depressive-like behaviors in adulthood (Barua et al, 2014;Trezza et al, 2008;Veronesi et al, 2017). A recent study reported that prenatal exposure to polychlorinated biphenyls (PCBs) significantly affected USVs produced by rats during affiliative interactions in adolescence and sociosexual interactions in adulthood (Bell et al, 2016).…”
Section: Ultrasonic Vocalizationsmentioning
confidence: 99%